KINSHIP RELATIONSHIP BETWEEN MANDAILING AND TOBA LANGUAGES: A COMPARATIVE HISTORICAL LINGUISTIC STUDY - Zainuddin; Ratna Dewanti (Rahis Cendekia Indonesia, 2024)
This study aims to analyze the kinship between Mandailing and Toba languages ​​through a comparative historical linguistics approach. This study uses a descriptive qualitative method by collecting basic vocabulary data from semantic categories such as body parts, numbers, and natural terms. Lexicostatistics techniques are applied to measure the level of vocabulary similarity, while phonological analysis is carried out to identify sound change patterns. The results of the study indicate that the level of basic vocabulary similarity between Mandailing and Toba languages ​​reaches **65% to 70%**, indicating a close genealogical relationship. Mandailing tends to maintain conservative forms, while Toba shows more innovation in sound patterns and vocabulary structures. Sound change processes such as syncope and assimilation are found as common patterns in the evolution of both languages. Differences in vocabulary and phonological patterns reflect the influence of geographical isolation and cultural interaction, such as the influence of Malay on Mandailing and Batak customs on Toba. This study concludes that Mandailing and Toba have the same linguistic roots in the Austronesian family, but have developed into separate linguistic systems due to the socio-cultural dynamics of their speaking communities. This study provides an important contribution to the study of language kinship in Indonesia and the preservation of regional languages ​​as cultural heritage.